Access to improved sanitation and health expenditure in Indonesia: An empirical analysis - Adrian Chrisnahutama (Journal of Economics Research and Policy Studies, 2026)
Health expenditure remains one of the main determinants of financial burdens for households in developing countries, including Indonesia. While previous studies have documented the health benefits of improved sanitation, there is still limited evidence regarding its economic consequences. Understanding this relationship is crucial for designing effective policies to both improve public health and alleviate financial burden. This study aims to examine the effect of access to improved sanitation on household health expenditure in Indonesia and to investigate whether this effect varies across regions with different levels of infrastructure development. Using the 2019 National Socioeconomic Survey (Susenas), this study finds that access to improved sanitation significantly reduces the likelihood of experiencing health problems, which in turn lowers health expenditure. The effect is substantially larger and statistically significant outside Java-Bali, where baseline sanitation coverage is lower and health risks are higher. Conversely, the effect is insignificant in the rest of Indonesia apart from Java-Bali, suggesting diminishing marginal returns in areas with relatively advanced infrastructure.